2013
DOI: 10.1002/jrs.4348
|View full text |Cite
|
Sign up to set email alerts
|

Raman and surface enhanced Raman scattering of a black dyed silk

Abstract: Artículo de publicación ISIThe Raman and surface enhanced Raman scattering (SERS) spectra of a black dyed silk sample (BDS) were registered. The spectral analysis was performed on the basis of Raman and SERS spectral data of isolated samples of Bombyx mori silk fibroin, its motif peptide component (GAGAGS) and the synthetic reactive black 5 dye (RB5). The macro FT-Raman spectrum of the silk sample is consistent with a silk II-Cp crystalline fraction of Bombyx mori silk fibroin; the SERS spectrum is highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
(81 reference statements)
1
18
0
Order By: Relevance
“…As shown in our previous work [8], the GAGAGS sequence is highly expressed in the cocoon fibroin. The Raman spectrum of the raw Bombyx mori silk (CS) has many similarities with the spectral profile of the peptide GAGAGS; thus, the crystal fraction dominates the spectrum.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…As shown in our previous work [8], the GAGAGS sequence is highly expressed in the cocoon fibroin. The Raman spectrum of the raw Bombyx mori silk (CS) has many similarities with the spectral profile of the peptide GAGAGS; thus, the crystal fraction dominates the spectrum.…”
Section: Resultsmentioning
confidence: 80%
“…In our recent publication concerning the RB5 dyed silk we observed that the Raman spectrum is dominated by the dye [8]. Three historic samples of dyed silks were analysed.…”
Section: Black Dyed Silksmentioning
confidence: 99%
See 1 more Smart Citation
“…A second group includes samples of dark silk belonging to the same period as the light samples, but differentiated by a lesser degradation with respect to the stability of the textiles. Samples of Bombyx mori silk fibroin, and its motif peptide component (GAGAGS) were also studied by using mainly Raman and surface enhanced Raman scattering (SERS) techniques [67]. Silk degumming, weighting and dyeing processes effects on the degradation of Bombyx mori silk fibroin were investigated through the ATR-IR and Raman techniques along with SEM/EDS microscopy.…”
Section: Historical Silksmentioning
confidence: 99%
“…The Raman spectrum of the raw Bombyx mori silk (CS), has many similarities with the spectral profile of the peptide GAGAGS, the crystal fraction dominating the spectrum [67]. The ATR-IR spectrum of the raw silk shows two strong bands at 1617 and 1511 cm −1 .…”
Section: Historical Silksmentioning
confidence: 99%